Decreased peripheral blood memory B cells are associated with the presence of interstitial lung disease in rheumatoid arthritis: a case-control study. Issue 1 (2nd January 2021) - Shimizu, Toshiaki; Nagafuchi, Yasuo; Harada, Hiroaki; Tsuchida, Yumi; Tsuchiya, Haruka; Hanata, Norio; Tateishi, Shoko; Kanda, Hiroko; Sumitomo, Shuji; Shoda, Hirofumi; Yamamoto, Kazuhiko; Fujio, Keishi
Abstract: Objectives: Interstitial lung disease sometimes occurs in rheumatoid arthritis patients. Although the underlying immunological mechanisms responsible for interstitial lung disease associated with rheumatoid arthritis have not yet been clarified, some reports have suggested possible roles of B cells. To examine the role of B-cell subsets in interstitial lung disease in rheumatoid arthritis patients, we analyzed peripheral blood B-cell subsets. Methods: We analyzed the frequencies of the peripheral blood B-cell subsets by flow cytometry in rheumatoid arthritis patients with and without interstitial lung disease ( n  = 16 and 81, respectively) and in healthy donors ( n  = 110) by high-resolution computed tomography. Results: Compared with healthy donors, rheumatoid arthritis patients showed statistically higher frequencies of naive B cells and lower frequencies of memory B cells. Moreover, the frequencies of memory B cells were lower in rheumatoid arthritis patients with interstitial lung disease than in those without. Multivariate analysis showed that the frequency of memory B cells, particularly switched memory B cells, was significantly decreased in rheumatoid arthritis patients with interstitial lung disease, even after adjusting for prednisolone dose. Conclusions: We suspect memory B cells play important roles in interstitial lung disease associated with rheumatoid arthritis.